Modeling the Transmission of COVID-19: Impact of Mitigation Strategies in Prekindergarten-Grade 12 Public Schools, United States, 2021. Issue 1 (30th January 2022) - Miller, Gabrielle F.; Greening, Bradford; Rice, Ketra L.; Arifkhanova, Aziza; Meltzer, Martin I.; Coronado, Fátima
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Background: Schools are an integral part of the community; however, congregate settings facilitate transmission of SARS-CoV-2, presenting a challenge to school administrators to provide a safe, in-school environment for students and staff. Methods: We adapted the Centers for Disease Control and Prevention's COVIDTracer Advanced tool to model the transmission of SARS-CoV-2 in a school of 596 individuals. We estimate possible reductions in cases and hospitalizations among this population using a scenario-based analysis that accounts for ( a ) the risk of importation of infection from the community; ( b ) adherence to key Centers for Disease Control and Prevention–recommended mitigation strategies: mask wearing, cleaning and disinfection, hand hygiene, and social distancing; and ( c ) the effectiveness of contact tracing interventions at limiting onward transmission. Results: Low impact and effectiveness of mitigation strategies (net effectiveness: 27%) result in approximately 40% of exposed staff and students becoming COVID-19 cases. When the net effectiveness of mitigation strategies was 69% or greater, in-school transmission was mostly prevented, yet importation of cases from the surrounding community could result in nearly 20% of the school's population becoming infected within 180 days. The combined effects of mitigation strategies and contact tracing were able to prevent most onward transmission. Hospitalizations were low among children and adults (<0.5% of the school population) across all scenarios examined. Conclusions: Based on our model, layering mitigation strategies and contact tracing can limit the number of cases that may occur from transmission in schools. Schools in communities with substantial levels of community spread will need to be more vigilant to ensure adherence of mitigation strategies to minimize transmission. Our results show that for school administrators, teachers, and parents to provide the safest environment, it is important to utilize multiple mitigation strategies and contract tracing that reduce SARS CoV-2 transmission by at least 69%. This will require training, reinforcement, and vigilance to ensure that the highest level of adherence is maintained over the entire school term.